A Box element to model semi-rigid connections in shell-based thin-walled structures analysis. (1st November 2021) - Soares, Henrique Barbosa; Paccola, Rodrigo Ribeiro; Coda, Humberto Breves
Highlights: Shell-based thin-walled structures modeling with semi-rigid connections. Generalized joints modeled by simple bracing panels. Box FE for automatic slabs × beams × columns connections. Buckling loads and critical points analysis. Instability and geometrical nonlinear path-following analysis. Abstract: In this study, we develop and propose a finite element (Box Element) designed specially to improve the shell-based simulation of elastic thin-walled structures. The Box Element (BE) allows a simple and automatic connection between beams and columns, as well as, between slabs and beams. The BE stiffness is assembled by bracing panels immersed in its numerical structure simulating the flexibility of connections. Its formulation is developed using an in house positional FEM code, whose 3D rotation degrees of freedom are replaced by generalized vectors, facilitating bending couplings and large rotation modeling. Instability and geometrical nonlinear path-following analysis are studied in examples, comparing results with literature benchmarks and proposing a practical application.